Towards a global perspective of environmental health: defining the research grounds of an institute of environmental health - Virgolino, A.; Antunes, F.; Santos, O.; Costa, A.; De Matos, M. G.; Bárbara, C.; Bicho, M.; Caneiras, C.; Sabino, R.; Núncio, M. S.; Matos, O.; Santos, R. R.; et al. (Sustainability, 2020)
Environmental health is at the intersection between health and the environment. However, it still has a recent (and narrow) history as a scientific area, mainly addressing human biomonitoring and toxicological issues. Only recently additional environmental ‘layers’, other than the traditional chemical, biological and physical environmental determinants, have been considered. This broader perspective of environmental health also encompasses digital, psychosocial, political, socioeconomic and cultural determinants, all of them relevant when considering human health from a planetary health paradigm. This reflects the progressive adoption of a systemic perspective regarding the impact of gains for human health and well-being towards a sustainable environment. It also implies a multi-method and participatory approach to understand the intertwined relationship between environmental changes and human health. In this paper, the broader approach to environmental health is discussed in order to ‘set the stage’ for introducing the Institute of Environmental Health (ISAMB) of the Lisbon School of Medicine, Portugal. Each of the research groups and labs that compose ISAMB are presented, as well as their main lines of research. Present and planned contributions of ISAMB to advance knowledge on environmental health and for promoting human health gains in an environmentally sustainable way are also discussed.